Genetic diversity of Potato virus M (PVM) in the major potato growing region in the Indo-Gangetic plain and characterization of a distinct strain of PVM occurring in India - Kumar, Alok; Katiyar, Akshay; Jailani, A. Abdul Kader; Chackraborty, Ashis; Mandal, Bikash (Frontiers in Microbiology, 2023)
Potato virus M (PVM) is one of the most prevalent viruses infecting potatoes worldwide, showing a wide range of diversity in their populations; however, the diversity and genome information of PVM occurring in India is hardly known. The present study serologically detected the PVM in 22.8% of leaf samples collected from the potato fields, generated 13 coat protein (CP) genes and one complete genome sequence for the isolates from India, and identified four differential hosts confirming PVM-Del-144 as a distinct strain of PVM occurring in India. The phylogenetic analyses conducted based on the CP gene sequences (14 from India and 176 from other countries) suggested the existence of three evolutionary divergent lineages (PVM-o, PVM-d, and a new divergent group) in the PVM population, where isolates from India belong to only two clusters (PVM-o and PVM-d) within four sub-clusters. High levels of nucleotide diversity (0.124) and genetic distance (0.142) recorded among the isolates from India may be due to the deviation from the neutral evolution and experiencing population expansion in the past. The complete genome of the isolate Del-144 (KJ194171; 8,526 nucleotides) shared 92.2–93.9% nt sequence identity with the population of PVM-o, whereas it shared only 70.2–72.1% identity with PVM-d. In the phylogenetic analyses, Del-144 clustered with the isolates of PVM-o; however, it formed a separate branch away from all other isolates, indicating the diversity of the strain. Overall, this study revealed the diversity of the isolates of PVM from India and reported the first complete genome sequence of a distinct strain of PVM occurring in India.